The 2016 oxide electronic materials and oxide interfaces roadmap. (3rd October 2016) - Lorenz, M; Ramachandra Rao, M S; Venkatesan, T; Fortunato, E; Barquinha, P; Branquinho, R; Salgueiro, D; Martins, R; Carlos, E; Liu, A; Shan, F K; Grundmann, M; et al.
Abstract: Oxide electronic materials provide a plethora of possible applications and offer ample opportunity for scientists to probe into some of the exciting and intriguing phenomena exhibited by oxide systems and oxide interfaces. In addition to the already diverse spectrum of properties, the nanoscale form of oxides provides a new dimension of hitherto unknown phenomena due to the increased surface-to-volume ratio. Oxide electronic materials are becoming increasingly important in a wide range of applications including transparent electronics, optoelectronics, magnetoelectronics, photonics, spintronics, thermoelectrics, piezoelectrics, power harvesting, hydrogen storage and environmental waste management. Synthesis and fabrication of these materials, as well as processing into particular device structures to suit a specific application is still a challenge. Further, characterization of these materials to understand the tunability of their properties and the novel properties that evolve due to their nanostructured nature is another facet of the challenge. The research related to the oxide electronic field is at an impressionable stage, and this has motivated us to contribute with a roadmap on 'oxide electronic materials and oxide interfaces'. This roadmap envisages the potential applications of oxide materials in cutting edge technologies and focuses on the necessary advances required to implement these materials, including both conventional and novel techniques for the synthesis, characterization, processing and fabrication of nanostructured oxides and oxide-based devices. The contents of this roadmap will highlight the functional and correlated properties of oxides in bulk, nano, thin film, multilayer and heterostructure forms, as well as the theoretical considerations behind both present and future applications in many technologically important areas as pointed out by Venkatesan. The contributions in this roadmap span several thematic groups which are represented by the following authors: novel field effect transistors and bipolar devices by Fortunato, Grundmann, Boschker, Rao, and Rogers; energy conversion and saving by Zaban, Weidenkaff, and Murakami; new opportunities of photonics by Fompeyrine, and Zuniga-Perez; multiferroic materials including novel phenomena by Ramesh, Spaldin, Mertig, Lorenz, Srinivasan, and Prellier; and concepts for topological oxide electronics by Kawasaki, Pentcheva, and Gegenwart. Finally, Miletto Granozio presents the European action 'towards oxide-based electronics' which develops an oxide electronics roadmap with emphasis on future nonvolatile memories and the required technologies. In summary, we do hope that this oxide roadmap appears as an interesting up-to-date snapshot on one of the most exciting and active areas of solid state physics, materials science, and chemistry, which even after many years of very successful development shows in short intervals novel insights and achievements. Guest editors: M S Ramachandra Rao and Michael Lorenz